2007
DOI: 10.1177/2156759x0701000409
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incidents in the Development of Supportive Principals: Facilitating School Counselor-Principal Relationships

Abstract: The qualitative study in this article explores critical incidents that may facilitate the support a principal provides for a school counseling program. Through structured interviews, supportive principals are asked to reflect on their prior experiences with school counselors, their educational exposure to school counseling, and their recommendations for school counselors. Results suggest that by demonstrating effective leadership and systemic interactions, school counselors can foster relationships with princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…Some participants described promotive school cultures that facilitated their ability to implement multicultural education behaviors, while others reported prohibitive school cultures that yielded challenges preventing them from enacting such behaviors. This finding aligns with previous research in which school counselors indicated that support from their administrators and other stakeholders is crucial to implementing effective comprehensive school counseling programs (Boyland et al, 2019; Dollarhide et al, 2007; Duslak & Geier, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Some participants described promotive school cultures that facilitated their ability to implement multicultural education behaviors, while others reported prohibitive school cultures that yielded challenges preventing them from enacting such behaviors. This finding aligns with previous research in which school counselors indicated that support from their administrators and other stakeholders is crucial to implementing effective comprehensive school counseling programs (Boyland et al, 2019; Dollarhide et al, 2007; Duslak & Geier, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…This may have added to the parental distrust or cultural misunderstandings that evolved in their counseling roles. Ironically, these challenges related to principals (Dollarhide et al 2007;Shoffner and Williamson 2000) and parents (Huss et al 2008;Field and Kolbert 2006), are revealed in typical schools in the USA as well, and point to a major gap in the school counseling field. Although academic programs may do a good job with educating school counselors about the unique skills needed to work with students, a greater focus on the role of consultation and collaborative relationships in the school community may be needed across the curriculum.…”
Section: Discussionmentioning
confidence: 96%
“…School counselors and principals can help each other in various ways, given the unique skillsets they have to offer. Dollarhide et al (2007) recommend school counselors talk with their principals to discuss expectations and how they see their role in the school setting. Communication between principal and school counselor can bring about a mutual understanding on how to improve academic achievement in turnaround schools.…”
Section: Recommendationsmentioning
confidence: 99%